Modal mineralogy of CI and CI-like chondrites by X-ray diffraction. (15th September 2015) - King, A.J.; Schofield, P.F.; Howard, K.T.; Russell, S.S.
Abstract: The CI chondrites are some of the most hydrated meteorites available to study, making them ideal samples with which to investigate aqueous processes in the early Solar System. Here, we have used position-sensitive-detector X-ray diffraction (PSD-XRD) to quantify the abundance of minerals in bulk samples of the CI chondrite falls Alais, Orgueil and Ivuna, and the Antarctic CI-like chondrites Y-82162 and Y-980115. We find that Alais, Orgueil and Ivuna are dominated by a mixed serpentine/saponite phyllosilicate (81–84 vol%), plus minor magnetite (6–10%), sulphides (4–7%) and carbonates (<3%). This reflects an extended period of aqueous alteration and the near-complete transformation of anhydrous phases into a secondary mineral assemblage. The similarity in total abundance of phyllosilicate suggests that the CI chondrites all experienced the same degree of aqueous alteration on the parent body. In contrast, Y-82162 contains a highly disordered serpentine/saponite phyllosilicate (68 vol%), sulphide (19%), olivine (11%) and magnetite (2%). This mineralogy is distinct from that of the CI chondrites, attesting to both a different starting mineralogy and alteration history. The structure and relatively low abundance of the phyllosilicate, and the high abundance of olivine, are consistent with previous observations that Y-82162 represents CI-like material that following aqueous alteration suffered thermal metamorphism at temperatures >500 °C. Similarly, Y-980115 contains disordered serpentine/saponite (71 vol%), sulphide (19%), olivine (8%) and magnetite (2%), confirming that it too is a thermally metamorphosed CI-like chondrite. We suggest that the CI-like chondrites are derived from a different parent body than the CI chondrites, which underwent short-lived thermal metamorphism due to impacts and/or solar radiation.